Kingdom of Morocco Systematic Country Diagnostic : Governing Towards Efficiency, Equity, Education and Endurance - World Bank Group (World Bank, Washington, DC, 2018)
Over the last 15 years, thanks to pro-poor growth performance, investment in education, health and other social services, and the deployment of social safety nets, Morocco has succeeded in eliminating extreme poverty, reducing poverty and to a lesser degree sharing prosperity. Yet, to make further poverty reduction progress, grow the middle class and meet the economic, social and societal aspirations of Moroccan youth, women and other vulnerable segments of society, Morocco needs to pursue a higher and more sustainable and inclusive pattern of economic growth that promotes job creation. The current growth model, however, shows signs of weaknesses as it is confronted with a series of sustainability issues (from economic to financial, territorial, environmental or social) that risk, with varying degrees of intensity, impeding progress toward emergence. Growth in the past two decades has been mainly based on public capital accumulation that will be difficult to maintain without higher total factor productivity gains in the future. The Systematic Country Diagnostic (SCD) identifies the multifaceted lack of inclusion as the central factor preventing the emergence of a more dynamic private sector and the realization of higher productivity gains. This entails the lack of inclusive market institutions, lack of inclusive public institutions, lack of inclusive human capital formation, and lack of inclusive social capital and opportunities for the youth, women and citizens in general. The SCD then proposes four pathways to govern toward greater efficiency, equity, education and endurance. These pathways aim at getting Morocco closer to its efficiency frontier (through competition and innovation, a more business-friendly environment, improved public policy formulation and coordination, and better access to quality public services); leveraging the efficiency frontier for all (through labor market reforms, better targeted social protection and increased gender equity); pushing the efficiency frontier (through successful human capital formation and better management of urbanization), and greening the efficiency frontier (through integrated water management and climate change adaptation). In the spirit of the 2011 Constitution, the SCD then considers that a change in Morocco’s system of governance (through access to information and accountability, voice and participation, and rule of law and justice) is required as the overarching cross-cutting pathway to make all the others possible.